2014
DOI: 10.1179/2047773214y.0000000130
|View full text |Cite
|
Sign up to set email alerts
|

Protective or pathogenic effects of vascular endothelial growth factor (VEGF) as potential biomarker in cerebral malaria

Abstract: Cerebral malaria (CM) is the major lethal complication of Plasmodium falciparum infection. It is characterized by persistent coma along with symmetrical motor signs. Several clinical, histopathological, and laboratory studies have suggested that cytoadherence of parasitized erythrocytes, neural injury by malarial toxin, and excessive inflammatory cytokine production are possible pathogenic mechanisms. Although the detailed pathophysiology of CM remains unsolved, it is thought that the binding of parasitized er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…VEGF plays a significant role in controlling the neoplastic angiogenic process. Recent studies have confirmed that VEGF promotes the growth of arterial, venous and lymphatic endothelial cells both in vitro and in vivo and promotes the survival and migration of endothelial cells (35,36). In our study, we demonstrated that Ad.RGD-ING4-PTEN inhibits CD34 and VEGF expression and reduces MVD in s.c. xenografted CNE human NPC tumors.…”
Section: Discussionsupporting
confidence: 76%
“…VEGF plays a significant role in controlling the neoplastic angiogenic process. Recent studies have confirmed that VEGF promotes the growth of arterial, venous and lymphatic endothelial cells both in vitro and in vivo and promotes the survival and migration of endothelial cells (35,36). In our study, we demonstrated that Ad.RGD-ING4-PTEN inhibits CD34 and VEGF expression and reduces MVD in s.c. xenografted CNE human NPC tumors.…”
Section: Discussionsupporting
confidence: 76%
“…have demonstrated the ability of intracerebral antigen-specific CD8 + T to initiate central nervous system vascular leakage through a perforin-dependent mechanism involving VEGF, that down-regulates tight junction proteins 12–24 hours before activation of the apoptotic caspase cascade [ 64 ]. Notably, VEGF is increased in the brains of mice with ECM [ 65 ] and humans with CM [ 66 , 67 ] and has been shown to inhibit endothelial cell apoptosis [ 68 70 ]. This scenario provides a potential explanation for the rapid recovery from ECM and reestablishment of the vascular integrity that can occurs after administration of anti-malarial drugs, which would not be possible if vascular dysfunction was mediated through extensive loss of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…CM is diagnosed by the existence of P. falciparum and functional changes. There is no biological test available to confirm human CM 45 .…”
Section: Discussionmentioning
confidence: 99%